(untitled) (Sahel Journal of Life Sciences FUDMA, 2024)
This study evaluated how traditional beliefs in Vandeikya Local Government Area, Benue State, contribute to the preservation of forest resources in Ikyo Maaki and Tse Gaver community forests. Purposive sampling procedure was used to select 6 communities, 3 communities in Ikyo Maaki and 3 communities Tse Gavar, the selection was based on their proximity to these community forests. In each of the selected community 25 persons were randomly selected from the key informants. This gives sampling intensity of 150 respondents, however only 133 questionnaires were retrieved. Data were collected with the aid of semi- structured questionnaire. Descriptive statistics and five points Likert scale were used to analyse the data collected. It was established that, restriction of access to the community forests, ban on felling of live trees in the community forests, ban on hunting in the forest, Ban on Killing of Mona Monkey, Restriction of pregnant women from entering the forest and enactment of traditional rules and regulations as well as sanction and fines were traditional practices used for the conservation of their community forests. The respondents agreed (WMS=3.74) that traditional beliefs were used as tools for forest conservation. Traditional beliefs were every effective in the conservation forest resources (WMS=4.44), those enforcing them were effective (WMS=3.77). Payment of high fines was one of the effective sanctions used (WMS=3.76). Traditional beliefs and practices were very effective of the community forests, it was recommended that such practices should be harnessed by relevant authorities for the management of our declined natural resources.